Moroccan Diaspora in France and the February 20 Movement in Morocco. Issue 3 (2nd July 2016) - Dumont, Antoine
ABSTRACT: This article analyzes the links between the so-called 20 February 2011 Movement in Morocco and the Moroccan migrant organizations in France. The research examines how the 50-year-long history of these organizations shapes Moroccan migrants' political experiences and their ties to homeland in order to explain why they do not play a significant role in the events unfolding in Morocco in 2011. To this end, concepts such as diaspora and transnationalism are mobilized to grasp how activists are connecting to places and territories and reducing the distance between them, while preserving a certain unity in their collective action.